2016
DOI: 10.1002/biot.201600337
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant flavin‐dependent halogenases are functional in tobacco chloroplasts without co‐expression of flavin reductase genes

Abstract: Halogenation of natural compounds in planta is rare. Herein, a successful engineering of tryptophan 6-halogenation into the plant context by heterologous expression of the Streptomyces toxytricini Stth gene and localization of its enzymatic product in various tobacco cell compartments is described. When co-expressed with the flavin reductase rebF from Lechevalieria aerocolonigenes, Stth efficiently produced chlorinated tryptophan in the cytosol. Further, supplementation of KBr yielded the brominated metabolite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 33 publications
5
39
0
Order By: Relevance
“…Recently, it has been shown that FDHs can be targeted to the chloroplasts in planta . Because chloroplasts contain naturally occurring reductases, there was no need for heterologous reductases (92). …”
Section: Flavin-dependent Halogenases (Fdhs)mentioning
confidence: 99%
“…Recently, it has been shown that FDHs can be targeted to the chloroplasts in planta . Because chloroplasts contain naturally occurring reductases, there was no need for heterologous reductases (92). …”
Section: Flavin-dependent Halogenases (Fdhs)mentioning
confidence: 99%
“…The tryptophan 5‐halogenase gene was chosen because PyrH showed the highest activity of the three halogenases with IAA (Figure S2). In previously published transformations of plants with bacterial halogenase genes, codon optimized halogenase genes had been used ,. In contrast to these experiments, we used native pyrH as well as pyrH with codons optimized for A. thaliana .…”
Section: Resultsmentioning
confidence: 99%
“…These experiments highlight the potential of combining the rich chemistry of plant metabolism with bacterial halogenases to generate unnatural products. Recently, the transient expression of another halogenase gene stth , coding for a tryptophan 6‐halogenase from Streptomyces toxytricini , in tobacco was reported and the authors showed that co‐expression of a tryptophan decarboxylase gene with this halogenase resulted in the production of chlorinated tryptamine …”
Section: Introductionmentioning
confidence: 99%
“…A similar study where RebH and Trp-6-halogenase SttH 44 were expressed in Nicotiana benthamiana revealed that the localization of the FDH/FR system to the chloroplasts could aid cofactor regeneration. 45 Localization of halogenases to the chloroplasts in the absence of exogenous FR led to comparable product formation indicating that the plastids provide a sufficient supply of reducing agents from native metabolic pathways. 46 The targeted coexpression of the Trp decarboxylase was required for production of halogenated tryptamine derivatives as the chloroplasts are devoid of this enzyme.…”
Section: Halogenase Engineeringmentioning
confidence: 96%